2020
DOI: 10.1111/anae.15094
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial comparing deep neuromuscular blockade reversed with sugammadex with moderate neuromuscular block reversed with neostigmine

Abstract: Summary Deep neuromuscular block aims to improve operative conditions during laparoscopic surgery with a lower intra‐abdominal pressure. Studies are conflicting on whether meaningful improvements in quality of recovery occur beyond emergence, and whether lower intra‐abdominal pressure is achieved. In this pragmatic randomised trial with 1:1 allocation, adults undergoing elective laparoscopic surgery were allocated to moderate neuromuscular block reversed with neostigmine, or deep neuromuscular block reversed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…In total, 265 studies were retrieved (Medline via PubMed), as well as 65 from the EMBASE database. After applying the eligibility criteria and evaluating titles and abstracts, 55 studies were selected, of which 36 were included 5-40 for evaluation of the full text and inclusion in the meta-analysis, with 19 studies excluded [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] (Figure 1). Three studies retrieved from EMBASE (Quang 5 , Lemmens 6 and Woo 7 ) were also found in the Medline search via PubMed.…”
Section: Resultsmentioning
confidence: 99%
“…In total, 265 studies were retrieved (Medline via PubMed), as well as 65 from the EMBASE database. After applying the eligibility criteria and evaluating titles and abstracts, 55 studies were selected, of which 36 were included 5-40 for evaluation of the full text and inclusion in the meta-analysis, with 19 studies excluded [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] (Figure 1). Three studies retrieved from EMBASE (Quang 5 , Lemmens 6 and Woo 7 ) were also found in the Medline search via PubMed.…”
Section: Resultsmentioning
confidence: 99%
“…34 However, several studies reported that the use of deep NMB alone without the application of a low IAP did not improve surgical conditions, postoperative pain, or quality of recovery after laparoscopic surgery. [35][36][37] A previous study suggested that the combination of deep NMB and low IAP reduced shoulder pain after laparoscopic hysterectomy. 38 A recent study showed that a low IAP did not lead to lower postoperative pain scores but reduced fentanyl requirement and the incidence of PONV in the recovery room after laparoscopic cholecystectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Seven studies were judged to be at low risk of bias [17,23,26,28,31,40,53], 23 studies were judged to raise some concerns [12, 15, 16, 19, 24, 29, 32, 34, 36, 38, 41-47, 49-52, 54, 55], and 10 studies were judged to be at high risk of bias [13,14,25,27,30,33,35,37,39,48]. The details of judgments for each risk-of-bias domain are demonstrated in Fig 2.…”
Section: Quality Assessment Of Included Studiesmentioning
confidence: 99%
“…In terms of the risk of bias, there were few studies at low risk of bias (7 RCTs, 17.5%) [17,23,26,28,31,40,53]. Some studies were judged to have some concerns about the risk of bias (23 RCTs, 57.1%) [12, 15, 16, 19, 24, 29, 32, 34, 36, 38, 41-47, 49-52, 54, 55].…”
Section: Plos Onementioning
confidence: 99%